Game developer : the leading game industry magazine. (San Francisco : CMP)
Game Developer, the print publication written specifically for creators of entertainment software, provides technical and industry information to over 35,000 professional game developers. Each month, industry leaders and game development experts share technical solutions, review new products, and discuss strategies for creating innovative, successful games. Professional game developers count on Game Developer magazine for the most relevant and respected content in the game industry.